2021
DOI: 10.21037/jtd-2021-07
|View full text |Cite
|
Sign up to set email alerts
|

Living-donor lobar lung transplantation

Abstract: Living-donor lobar lung transplantation (LDLLT) has become an important life-saving option for patients with severe respiratory disorders, since it was developed by a group in the University of Southern California in 1993 and introduced in Japan in 1998 in order to address the current severe shortage of brain-dead donor organs. Although LDLLT candidates were basically limited to critically ill patients who would require hospitalization, the long-term use of steroids, and/or mechanical respiratory support prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, because of the expanded utilization of the lung allocation scoring system and expanded donation after circulatory death, 4,5 LDLLT is currently rarely performed in the United States and is only performed in a few other countries 6,7 . However, in Japan, LDLLT remains a practical option and has been performed in one‐third of lung transplantation procedures since the 1990s instead of deceased donor lung transplantation 8,9 . This finding is partly because deceased lung donors are scarce, resulting in high waiting list‐related mortality 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…However, because of the expanded utilization of the lung allocation scoring system and expanded donation after circulatory death, 4,5 LDLLT is currently rarely performed in the United States and is only performed in a few other countries 6,7 . However, in Japan, LDLLT remains a practical option and has been performed in one‐third of lung transplantation procedures since the 1990s instead of deceased donor lung transplantation 8,9 . This finding is partly because deceased lung donors are scarce, resulting in high waiting list‐related mortality 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…As with DBD and DCD donation, CLAD remains a significant barrier to long term survival in LDLLT. Date and colleagues reported the majority of their LDLLT recipients experienced unilateral CLAD however shown to develop later in postoperative period, proving the possible protective effect of using 2 donors for a single recipient [34,36,37]. In their most recent study, long-term survival after LDLLT was reported to be 73.3% at 15 years, with 5-year survival following diagnosis of CLAD still promising at 66.9% [36].…”
Section: Living-donor Lobar Lung Transplantationmentioning
confidence: 99%
“…Starnes and his colleagues at the University of Southern California (USC) in 1993, first reported the use of living-donor lobar lung transplantation (LDLLT) in extremely ill patients with a high risk of short-term waitlist mortality [32]. In LDLLT, with the use of 3 transplant teams, right and left lower lobes are resected from 2 healthy donors and implanted in recipient in place of the whole right and left lung, respectively [33,34]. Intermediate results proved promising in terms of functional outcome and survival [32].…”
Section: Living-donor Lobar Lung Transplantationmentioning
confidence: 99%
See 2 more Smart Citations